Mladinska fantastična pripoved in njena umestitev v koncept sodobne slovenske mladinske fantastične proze - Artnik, Gregor (Revija za elementarno izobraževanje, 2012)
Youth fantastic tale and its placement within the concept of contemporary Slovenian youth fantastic prose. This paper is an attempt to issue a challenge to genre typology of contemporary Slovenian fantastic prose for youth based on preliminary treatment of contemporary fantastic tale and related terminology. Its foundation is placed in thematic and structural characteristics of fantastic literature as supergenre. Regardless of the fact that Slovenian fantastic tale is often not as extensive as related texts in Western literature, there are also indications of genre fluidity which in the core of contemporary Slovenian fantastic tale for youth often merges mutually exclusive elements of dystopia, fantasy, horror, myth and science fiction.